2013
DOI: 10.1037/a0032011
|View full text |Cite
|
Sign up to set email alerts
|

Childless lesbian and gay adults’ self-efficacy about achieving parenthood.

Abstract: Lesbian and gay people are much less likely than others to become parents, and psychological factors may contribute to this difference. We explored self-efficacy about becoming a parent among geographically diverse, childless, lesbian and gay U.S. residents aged 18 to 44 years (n ϭ 1,098). On average, participants reported that they were uncertain whether they could overcome financial barriers to parenthood or become biological parents without assistance from reproductive health providers. However, they were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 43 publications
5
69
1
2
Order By: Relevance
“…Notable exceptions include a study done by Riskind, Patterson, and Nosek (2013), which found that sexual minorities living in unfavorable legal climates are more likely to express doubts that becoming a parent is possible. Likewise, Patterson and Riskind (2010) suggest that legal obstacles might impact which route to parenthood lesbians and gay men pursue.…”
Section: Legal Barriersmentioning
confidence: 99%
“…Notable exceptions include a study done by Riskind, Patterson, and Nosek (2013), which found that sexual minorities living in unfavorable legal climates are more likely to express doubts that becoming a parent is possible. Likewise, Patterson and Riskind (2010) suggest that legal obstacles might impact which route to parenthood lesbians and gay men pursue.…”
Section: Legal Barriersmentioning
confidence: 99%
“…It does suggest, however, that changes in social contexts, namely, more cultural and legal support for sexual minority women, would create a change in the parenting options that sexual minority women see as available to them. Indeed, Riskind, Patterson, and Nosek (2013) found that sexual minorities living in unfavorable social climates were more likely to express doubts about whether they thought they could become a parent. Future work should continue to address how social and legal contexts, along with race and class, might influence both how sexual minority women think about becoming parents (including whether or not they want to), as well as the routes and barriers to parenthood (Goldberg et al, 2009;Moore, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…There's, you know, Massachusetts, New York, and California" (p. 376). Other work underscores the finding that legal barriers can negatively impact LGBQ people's perceptions about their ability to become a parent (Brown, Smalling, Groza, & Ryan, 2009;Riskind, Patterson, & Nosek, 2013;Wall, 2011). For instance, based on analysis of survey data from 1,098 gays and lesbians without children, Riskind et al (2013) found that those living in favorable social and legal climates believed they could become parents while those in unfavorable social and legal climates were more likely to report doubts as to whether they could become parents.…”
Section: Social Barriersmentioning
confidence: 99%